Improved Outcomes With an Enhanced Recovery Approach to Cesarean Delivery. Issue 2 (24th June 2021) - Mullman, L.; Hilden, P.; Goral, J.; Gwacham, N.; Tauro, C.; Spinola, K.; Rosales, K.; Collier, S.; Holmes, L.; Maccione, J; Pitera, R.; Miller, R.; et al.
Abstract : ( Obstet Gynecol . 2020;136:685–691) To improve the quality of perioperative care and facilitate patients' quick recovery, a number of settings including gynecology have adopted enhanced recovery after surgery (ERAS) programs. These programs have been shown to have a positive impact on patients' quality of care on hospital utilization measures. However, there is limited data on the effectiveness of ERAS programs in women undergoing cesarean delivery (CD) including reducing need for opioids. The aim of this study was to evaluate an ERAS program on outcomes in women undergoing cesarean delivery.